Strong convergence theorem for a new general system of variational inequalities in Banach spaces - Suantai S. (2014)
We introduce a new system of general variational inequalities in Banach spaces. The equivalence between this system of variational inequalities and fixed point problems concerning the nonexpansive mapping is established. By using this equivalent formulation, we introduce an iterative scheme for finding a solution of the system of variational inequalities in Banach spaces. Our main result extends a recent result acheived by Yao, Noor, Noor, Liou, and Yaqoob. Copyright © 2010 S. Imnang and S. Suantai.